Pelaksanaan Pemilu yang Aksesibel dan Non-Diskriminasi sebagai Upaya Pemenuhan Hak-Hak Politik Penyandang Disabilitas - Junaidi Abdillah (Jurnal HAM, 2015)
Every citizen shall be involved in making policy and the state must protect these rights. Persons with disabilities as part of the citizens who are vulnerable to discrimination requires more protection and special treatment to be able to participate fully in the implementation of the general election on the basis of equal rights and opportunities with other citizens. This study will analyze how efforts to fulfill the rights of persons with disabilities Indonesian politics through elections that are not only implemented in direct , public , free, confidential , honest and fair, but must be accessible and non-discrimination for persons with disabilities. The method used in this research is using a qualitative approach, the technique of primary and secondary data collection, as well as conducting an inventory of the legislation with normative and empirical methods. Based on field data about the elections in Indonesia in 2004 until the 2014 elections a form of respect, protection and fulfillment of the political rights of persons with disabilities through elections accessible and non-diskrimanasi gradually have increased significantly although there are still barriers that limit and eliminating the political rights of persons with disabilities.